COMMUNITY STRUCTURE AND DIVERSITY OF PHYTOPLANKTON IN LEMUKUTAN ISLAND WATERS, WEST KALIMANTAN - Nora Idiawati; Ikha Safitri; Mega Sari Juane Sofiana (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2021)
Phytoplankton plays an important role in marine ecosystems as  primary producer, as the basis of food chains and the food web, and are widely used as bioindicators to monitor water condition. The study of phytoplankton is the primary interest to explore aquatic resources for blue biotechnology applications in conditions as a live feed, antibacterial, antiviral, antioxidant, pharmaceutical, cosmetics, possibly food and health industry. The study aims to assess the composition, abundance and diversity of phytoplankton community in Lemukutan Island waters of West Kalimantan. The present study found 31 genera of phytoplankton, consisted of Bacillariophyceae (28 genera) and Dinophyceae (3 genera). In term of contribution, Bacillariophyceae were found to be dominant (93.035%) than dinophyceae (6.965%). The abundance of phytoplankton varied between 636.91 to 2034.48 cell.L-1. The diversity index (H’), the evenness (E) index, and the dominance (C) index ranged from 1.959–2.579, 0.582–0.868, 0.094–0.283, respectively. The result showed that the diversity index was moderate, the evenness index was high, and the dominance index was low.